A Synthesis of the Research on Community Service Learning in Preservice Science Teacher Education - Khan, Samia A.; VanWynsberghe, Rob (Frontiers in Education, 2020)
Despite recent recommendations urging stronger connections between teacher education programs and their communities, few studies have examined the potential of community service learning (CSL) within science teacher education. The paper aims to: understand how CSL is conceptualized in preservice science teacher education contexts; identify the various ways that CSL is integrated within courses; examine stated outcomes for preservice science teachers, and; explore how research on CSL has been carried out in science teacher education. To better inform science teacher education, the authors embarked upon a research synthesis of relevant articles within preservice science teacher education. Six main findings emerged from the synthesis: 1) different science teacher education programs define CSL similarly, 2) preservice science teachers’ engagement with CSL is primarily reported as being beneficial, 3) mixed outcomes are reported in preservice teachers’ self-efficacy, confidence, and attitudes toward teaching science, 4) challenges, if reported, tend to be from the perspective of preservice teachers, 5) several common teaching strategies are employed to support the CSL experience, and 6) case study is the most typical research methodology for studying CSL, where the researchers are the instructors of their own CSL courses. These findings are significant for the ongoing development of science teacher knowledge and programmatic directions for the integration of community in science teacher education.